Storage dynamics in hydropedological units control hillslope connectivity, runoff generation, and the evolution of catchment transit time distributions. Issue 2 (6th February 2014) - Tetzlaff, D.; Birkel, C.; Dick, J.; Geris, J.; Soulsby, C.
Abstract We examined the storage dynamics and isotopic composition of soil water over 12 months in three hydropedological units in order to understand runoff generation in a montane catchment. The units form classic catena sequences from freely draining podzols on steep upper hillslopes through peaty gleys in shallower lower slopes to deeper peats in the riparian zone. The peaty gleys and peats remained saturated throughout the year, while the podzols showed distinct wetting and drying cycles. In this region, most precipitation events are <10 mm in magnitude, and storm runoff is mainly generated from the peats and peaty gleys, with runoff coefficients (RCs) typically <10%. In larger events the podzolic soils become strongly connected to the saturated areas, and RCs can exceed 40%. Isotopic variations in precipitation are significantly damped in the organic‐rich soil surface horizons due to mixing with larger volumes of stored water. This damping is accentuated in the deeper soil profile and groundwater. Consequently, the isotopic composition of stream water is also damped, but the dynamics strongly reflect those of the near‐surface waters in the riparian peats. "pre‐event" water typically accounts for >80% of flow, even in large events, reflecting the displacement of water from the riparian soils that has been stored in the catchment for >2 years. These riparian areas are the key zone where different source waters mix. Our study is novel in showing that they act as "isostats, " not only regulating the isotopic composition of stream water, but also integrating the transit time distribution for the catchment.